Phytochemical Screening and Antibacterial Activities of Senggani (Melastoma malabathricum L.) Ethanolic Extract Leaves - Retno Widowati; Sri Handayani; Ahmad Ridho Al Fikri (Institut Pertanian Bogor, 2021)
The aim of the current research was to perform phytochemical screening and to know the pathogenic antibacterial activities of senggani leaves extract. Phytochemical screening was done by testing eight active compounds. Antibacterial activities testing was done by using well diffusion method at concentration level of 25%, 50%, 75%, 100%. Positive control was amoxicillin, while the negative control was aquadest. Meanwhile, pathogenic bacteria were Escherichia coli, Shigella dysenteriae, Staphylococcus aureus, and Pseudomonas aeruginosa. Research design applied was complete random design, in which the data collected were analyzed using one-way ANOVA, continued by post-hoc test through Tukey method to know which concentration provide the most significant difference. Research results showed that ethanolic extract of senggani leaves has eight active compounds, those are phenolics, alkaloids, flavonoids, tannins, triterpenoids, glycosides, steroids, and saponins. This further proved that the ethanolic extract of senggani leaves have antibacterial activity and are able to inhibit the growth of all bacteria tested. The best ability shown to inhibit E. coli bacteria was at concentration of 100%, Sh. dysenteriae and P. aeruginosa started at the concentration of 75%, and S. aureus started at the concentration of 50%. Keywords: active compounds, bacteria growth, inhibition, well diffusion